The Econometric Modelling of Financial Time Series : Third edition - Mills, Terence C (Cambridge University Press, 2013)
The aim of this book is to provide the researcher in financial markets with the techniques necessary to undertake the empirical analysis of financial time series. To accomplish this aim we introduce and develop both univariate modelling techniques and multivariate methods, including those regression techniques for time series that seem to be particularly relevant to the finance area.